Menispermaceae endémicas del Perú - Ortiz-Gentry, Rosa (2006)
The Menispermaceae are represented in Peru by 15 genera and 75 species (Brako & Zarucchi, 1993; Ulloa Ulloa et al., 2004), mainly lianas and vines. Here we recognize four endemic species in three genera. These endemic species are found in Humid Lowland Amazonian Forests and Very Humid Montane Forests regions, between 100 and 940 m elevation. No endemic Menispermaceae have been registered today within Peru’s protected areas system.